Back Cover Image, Volume 15, Issue 1. (8th January 2021) - Xu, Chunbao Charles; Dessbesell, Luana; Zhang, Yongsheng; Yuan, Zhongshun
Abstract : The back cover image is based on the Review Article Lignin Beyond Energy ‐ Has Lignin's Time Finally Come? by Chunbao Charles Xu et al., https://doi.org/10.1002/bbb.2172 .